2012
DOI: 10.1111/j.2042-7158.2012.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the effects of diclofenac and other non-steroidal anti-inflammatory agents on ion channels

Abstract: Objectives Diclofenac and other non-steroidal anti-inflammatory drugs (NSAIDs) are widely used in the treatment of inflammation and pain. Most effects of NSAIDs are attributed to the inhibition of cyclooxygenases (COX). However, many NSAIDs may have other effects not related to COX, including the modulation of various ion channels. The clinical implications of the effects on channels are not fully understood. This review outlines the effects of NSAIDs, with special attention to diclofenac, on ion channels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 123 publications
(374 reference statements)
0
26
0
1
Order By: Relevance
“…[39]). Specifically, NSAIDs with ulcerogenic potential (indomethacin and NS-398), but not non-ulcerogenic NSAIDs (SC-560), decrease total and surface expression of K v 1.4 and surface expression of K v 1.6 in IEC-6 cell monolayers, and it was suggested that this loss of expression inhibited cell migration and caused depolarization of E m [18].…”
Section: Introductionmentioning
confidence: 99%
“…[39]). Specifically, NSAIDs with ulcerogenic potential (indomethacin and NS-398), but not non-ulcerogenic NSAIDs (SC-560), decrease total and surface expression of K v 1.4 and surface expression of K v 1.6 in IEC-6 cell monolayers, and it was suggested that this loss of expression inhibited cell migration and caused depolarization of E m [18].…”
Section: Introductionmentioning
confidence: 99%
“…It should be also noted that diclofenac can accumulate in inflamed tissues (Brune, 2007), and this drug is often applied topically on the skin at higher concentrations, especially in the inflamed area (Singh and Roberts, 1994). Diclofenac also inhibits ASICs to prevent the generation of acid-mediated action potentials at peripheral terminals (Gwanyanya et al, 2012;Voilley et al, 2001), and has side effects including cardiac toxicity because of its higher affinity to cardiac Na + channels (Fei et al, 2006). Thus, topical diclofenac could be useful for the treatment of inflammatory pain, such as ischemic myalgia and arthritis.…”
Section: Discussionmentioning
confidence: 98%
“…Diclofenac is known to modulate a number of ion channels including voltage-gated Na + , K + , and Ca 2+ channels (Gwanyanya et al, 2012). It inhibits both TTX-R and TTX-S Na + channels in dorsal root ganglion neurons (Lee et al, 2003), and other preparations (Acosta et al, 2007;Fei et al, 2006;Kuo et al, 2000;Yang and Kuo, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations